Evaluation of transgene expression characteristics and DNA vaccination against melanoma metastasis of an intravenously injected ternary complex with biodegradable dendrigraft poly-L-lysine in mice. (1st January 2021) - Kodama, Yukinobu; Tokunaga, Ayako; Hashizume, Junya; Nakagawa, Hiroo; Harasawa, Hitomi; Kurosaki, Tomoaki; Nakamura, Tadahiro; Nishida, Koyo; Nakashima, Mikiro; Hashida, Mitsuru; Kawakami, Shigeru; Sasaki, Hitoshi
Abstract: We developed a biocompatible splenic vector for a DNA vaccine against melanoma. The splenic vector is a ternary complex composed of plasmid DNA (pDNA), biodegradable dendrigraft poly-L-lysine (DGL), and γ-polyglutamic acid (γ-PGA), the selective uptake of which by the spleen has already been demonstrated. The ternary complex containing pDNA encoding luciferase (pCMV-Luc) exhibited stronger luciferase activity for RAW264.7 mouse macrophage-like cells than naked pCMV-Luc. Although the ternary complex exhibited strong luciferase activity in the spleen after its tail vein injection, luciferase activity in the liver and spleen was significantly decreased by a pretreatment with clodronate liposomes, which depleted macrophages in the liver and spleen. These results indicate that the ternary complex is mainly transfected in macrophages and is a suitable formulation for DNA vaccination. We applied the ternary complex to a pUb-M melanoma DNA vaccine. The ternary complex containing pUb-M suppressed the growth of melanoma and lung metastasis by B16-F10 mouse melanoma cells. We also examined the acute and liver toxicities of the pUb-M ternary complex at an excess pDNA dose in mice. All mice survived the injection of the excess amount of the ternary complex. Liver toxicity was negligible in mice injected with the excess amount of the ternary complex. In conclusion, we herein confirmed that the ternary complex was mainly transfected into macrophages in the spleen after its tail vein injection. We also showed the prevention of melanoma metastasis by the DNA vaccine and the safety of the ternary complex.